Análise acerca da discriminação de gênero contra encarcerados inseridos na co- munidade LGBTQIA+ - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2021)
Members of the LGBTQIA + inmates community are daily rejected socially and by the prison system itself. Their fundamental rights and guarantees are routinely violated for performing a phenotype which is not their birthright. The current binary modulation, according to the convicts are punished in the prison system in compliance with biological sex, demonstrates the State's inability to collect the incarcerated LGBT population, thus causing a double penalty, already added to social discrimination. The aim of the present work is, at first, to analyze the prison circumstances in which the aforementioned group, how the differentiated treatment given to these people by the State, through the non-compliance with national and international protective norms, and by society, through hate speech and violent acts, defilement or enjoyment of their dignity and the safeguarding of their physical, moral, psychological and emotional integrity. The methodology used consists of the inductive method of research, of an exploratory and descriptive nature, since, with emphasis on primary sources (such as current legislation, doctrine and jurisprudence dealing with the object), as well as secondary sources (such as books, articles, publications, specialties, reports made by the written press and official data published on the internet), will seek to describe, explain and clarify the aspects that involve the object of this study. In the end, it is intended to demonstrate inmates LGBTs, internal to the prison system or egress from it, provide more than those who do not belong to such group, since the intersectionality between their condition of imprisoned and their sexuality and gender identity makes them more vulnerable.
Keywords: Direitos humanos; Sexualidade; Identidade de gênero; LGBTfobia; Violências; CNPQ:: CIÊNCIAS SOCIAIS APLICADAS